ANALISIS VIBRASI PADA POMPA - Panjaitan, Felix Budianto; Suryadi, Dedi; Zuliantoni (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2023)
Vibration analysis is an effective machine maintenance method by analyzing signal characteristics and vibrations so that the condition and condition of the equipment can be identified. PT. The Pertamina International Refinery - Balikpapan is one of the business units of the Pertamina Refinery Directorate whose products are distributed to the eastern part of Indonesia which is 2/3 of the Republic of Indonesia and some products are distributed to the western part of Indonesia and exported. The benefit of the vibration method is to find out damage to the pump early and to avoid more severe damage to the pump. The research method is carried out by periodically monitoring an equipment (pump) with vibration analysis to see the condition of the machine under normal conditions until damage occurs. High vibrations occur at the DE point which is lower than the NDE point. Based on measurements, high vibration occurred at the NDE pump point on January 17, 2023 in the vertical direction – speed of 27,041 mm/s, horizontal direction – speed of 28.21 mm/s, horizontal direction – casing 28,539 mm/s, and axial direction – speed of 26.89mm/s. After analyzing the spectrum, it is known that the cause of high vibration in the pump is caused by bearings that are not working properly. And also because of the Random High Frequency on the spectrum, where the frequency occurs due to damage to the bearings. The overall vibration value in the DE and NDE positions after repair is within the permissible limits based on ISO 10186.